Acute Liver Failure Triggered by Therapeutic Dose of Acetaminophen in a Patient with Cystic Fibrosis. Issue 4 (April 2023) - Goodman, Adam; Grenn, Emily E.; Koller, Felicitas L.; Petrasek, Jan
Here we present the case of a cystic fibrosis (CF) patient with preserved pulmonary function who developed acute liver failure requiring liver transplant following an episode of binge drinking and ingestion of a modest amount of acetaminophen. Cystic Fibrosis Liver Disease (CFLD) is the third most common cause of death among CF patients. The pathogenesis of CFLD is complex and still not fully understood. It is important that patients suffering from CF know about the possible dangers associated with acetaminophen and ethanol ingestion. Our case report highlights the need for more research that needs to be done to truly understand the underlying pathogenesis of CFLD and the significant risk factors that play a part in the development of acute liver failure in patients with CF.